2004
DOI: 10.1002/aheh.200400539
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Condition of Urban Groundwater in the Vicinity of Leaky Sewer Systems

Abstract: The possible deterioration of the microbiological quality of groundwater due to leaky sewer systems was investigated in a medium‐sized city (Rastatt) in SW‐Germany. Specially constructed focus observation wells drilled close to leaky sewers have been compared with the background observation wells in urban and rural areas. The sampling was performed in March (shallow depth of groundwater) and in July and October (deep groundwater table). It included the measurement of ammonium ions, temperature, electric conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 12 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…The acifluorfen relative leaching ranks were developed by applying ArcPRZM-3 for 25 monitored well sites (i.e., 6, 7, 9, 10, 11 (6,23,36, and 43) was rice while it was soybean for all the others. The daily average dissolved acifluorfen concentrations were modeled at soil depth of 1.8 m for 25 well sites during the period of interest.…”
Section: Arcprzm-3 Application For Pesticide Relative Leaching Ranks mentioning
confidence: 99%
See 1 more Smart Citation
“…The acifluorfen relative leaching ranks were developed by applying ArcPRZM-3 for 25 monitored well sites (i.e., 6, 7, 9, 10, 11 (6,23,36, and 43) was rice while it was soybean for all the others. The daily average dissolved acifluorfen concentrations were modeled at soil depth of 1.8 m for 25 well sites during the period of interest.…”
Section: Arcprzm-3 Application For Pesticide Relative Leaching Ranks mentioning
confidence: 99%
“…The application of pesticides increases the crop productivity but it can also contaminate the groundwater sources [2][3][4][5][6][7][8]. Groundwater vulnerability assessment can be obtained by analyzing the pesticides leaching toward groundwater using the simulation models, e.g., depth to water, net recharge, aquifer media, soil media, topography, impact of vadose zone, and hydraulic conductivity (DRASTIC) [9], groundwater loading effects of agricultural management systems (GLEAMS) [10], HYDRUS-1D [11], leaching estimation and chemistry model (LEACHM) [12], PRZM [13], root zone water quality model (RZWQM) [14], hierarchical cluster analysis (HCA) [15], and groundwater modeling tool for grass (GMTG) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Microbiological tracers have been proposed to assess recharge by contaminated waters related to sewer water, landfills, runoff, etc. Powel et al, 2003;Paul et al, 2004;Vertraeten et al, 2005;Morris et al, 2006). Contaminated waters can also be identified by means of organic compounds, BTEX, PAH, metabolites, pharmaceuticals, etc.…”
Section: Tracer Selectionmentioning
confidence: 99%
“…Microbiological indicators Several groundwater observation wells in the urban area revealed coliforms, E. coli and enterococci as indicators for faecal contamination (Paul et al, 2004). Regarding the coliforms and E. coli the bacterial counts showed a strong correlation with the distance to the leakage, all three bacteria were found in highest concentrations in the focus observation wells close to major sewer leaks.…”
Section: 225mentioning
confidence: 99%
“…Table 5. Bacterial counts in groundwater samples according to the location of the groundwater monitoring well (Paul et al, 2004 As no obvious originator could be identified and the plumes extend along one of the main sewers it was considered that the contamination results from sewer leakage. Furthermore, trans-DCE in groundwater is only stable for a very short time as it is further degraded to vinylchloride so findings of trans-DCE in groundwater suggest a recent or permanent entry.…”
Section: Contamination Through Industrial Sewagementioning
confidence: 99%